The tangible & intangible cultural landscape of Wadi Bani Kharus : investigations in the Sultanate of Oman - Ibrahim, Moawiyah (Archaeopress Publishing Ltd, 2020)
The Tangible & Intangible Cultural Landscape of Wadi Bani Kharus: Investigations in the Sultanate of Oman presents the result of the project sponsored by Oman's Ministry of Heritage and Culture (now Heritage and Tourism) to survey one of the country's most significant valleys. The primary objective was to gain greater understanding of the area's past and present through its tangible and intangible cultural heritage. Traditional archaeological methods were bridged with those of cultural anthropology to create a wider lens for exploration and analysis. The book provides an eclectic overview of the wadi's twenty-nine communities including ancient fortresses and water distribution systems, sundials, cemeteries, tombstones and period architecture in addition to oral histories highlighting past lifeways and recent transformations.